Methamphetamine injecting is associated with phylogenetic clustering of hepatitis C virus infection among street-involved youth in Vancouver, Canada. (1st July 2015) - Cunningham, Evan B.; Jacka, Brendan; DeBeck, Kora; Applegate, Tanya L.; Harrigan, P. Richard; Krajden, Mel; Marshall, Brandon D.L.; Montaner, Julio; Lima, Viviane Dias; Olmstead, Andrea D.; Milloy, M.-J.; Wood, Evan; et al.
Highlights: This study investigates phylogenetic clustering of HCV infection and associated factors in a cohort of street-involved youth. Of the 65 participants, 14% ( n = 9) were in a cluster or pair, with all reporting recent methamphetamine injection. Methamphetamine injecting is associated with phylogenetic clustering ( P = 0.009). Results suggest that methamphetamine drug injection may play an important role in networks of HCV transmission. Abstract: Background: Among prospective cohorts of people who inject drugs (PWID), phylogenetic clustering of HCV infection has been observed. However, the majority of studies have included older PWID, representing distant transmission events. The aim of this study was to investigate phylogenetic clustering of HCV infection among a cohort of street-involved youth. Methods: Data were derived from a prospective cohort of street-involved youth aged 14–26 recruited between 2005 and 2012 in Vancouver, Canada (At Risk Youth Study, ARYS). HCV RNA testing and sequencing (Core-E2) were performed on HCV positive participants. Phylogenetic trees were inferred using maximum likelihood methods and clusters were identified using ClusterPicker (Core-E2 without HVR1, 90% bootstrap threshold, 0.05 genetic distance threshold). Results: Among 945 individuals enrolled in ARYS, 16% ( n = 149, 100% recent injectors) were HCV antibody positive at baseline interview ( n = 86) or seroconverted during follow-up ( n = 63). Among HCV antibody positive participants with available samples ( n = 131), 75% ( n = 98) had detectable HCV RNA and 66% ( n = 65, mean age 23, 58% with recent methamphetamine injection, 31% female, 3% HIV+) had available Core-E2 sequences. Of those with Core-E2 sequence, 14% ( n = 9) were in a cluster (one cluster of three) or pair (two pairs), with all reporting recent methamphetamine injection. Recent methamphetamine injection was associated with membership in a cluster or pair ( P = 0.009). Conclusion: In this study of street-involved youth with HCV infection and recent injecting, 14% demonstrated phylogenetic clustering. Phylogenetic clustering was associated with recent methamphetamine injection, suggesting that methamphetamine drug injection may play an important role in networks of HCV transmission.